THE PROMOTION OF THE CONCEPT OF RESPECT FOR DIVERSITY IN SCHOOLS AND SOCIETY THROUGH PEDAGOGICAL DESIGN BASED ON THE PERSPECTIVES OF A WOMAN ACADEMIA - Liah Rosdiani Nasution (IAIN Padangsidimpuan, 2020)
Â This article explores the journey of a woman in academia in the schooling contexts throughout her academic and professional course. This article specifically encourages those who teach in schools of education to accept greater responsibility for the inadequate preparation of educators for work in racially, religiously, ethnically, culturally, and linguistically diverse academic post-secondary institutions. Furthermore, this paper also invites educators to do more to make our findings actionable so we can contribute to the end of these educational inequities.Â